Outcome of pulse therapy in pemphigus: A 10-year study - Sirisha Varala; Shashikant Malkud; Geeta Kiran Arakkal; Divya Siddavaram (Wolters Kluwer Medknow Publications, 2018)
Background: Pemphigus is a potentially fatal autoimmune blistering disease affecting the skin and mucosa. Pulse therapy has been tried in pemphigus in India and other countries with variable results. Aims: The aim of the study was to assess the outcome of pulse therapy in pemphigus patients treated over a period of 10 years. Materials and Methods: Patients with pemphigus treated with pulse therapy from 2006 to 2016 were taken into the study. Results: A total of 122 pemphigus patients were included in the study, of which pemphigus vulgaris was diagnosed in 112 patients, pemphigus foliaceus in 9 patients, and pemphigus vegetans in 1 patient. The mean age was 37.75 ± 8.60 years, with an age range of 19-58 years. Duration of the disease ranged from 7 days to 3 years, with a mean of 6.87 ± 8.81 months. Ninety-three patients were started on dexamethasone cyclophosphamide pulse therapy and 29 on dexamethasone azathioprine pulse therapy. Thirty-three patients discontinued treatment, pulse therapy was stopped in two patients due to complications, and four patients died while on treatment. Out of the remaining 83 patients, 22 patients were in Phase I, 13 in Phase II, 7 in Phase III, and 41 in Phase IV by the end of the study. Sixty-one patients completed Phase I and were maintaining remission. Seven patients relapsed (3 in Phase II and 2 each in Phase III and IV). Ten patients completed 5 years of Phase IV and were considered cured of the disease. Generalized weakness, myalgia, headache, diabetes, and amenorrhea were the most common side effects. Conclusion: Pulse therapy was found to be effective in inducing and maintaining remission in the treatment of pemphigus. Prevention of relapses requires continuation of the treatment during Phase II and III.